Enhancing Junior High School Students’ Procedural Writing through Picture Series: A Pre-Experimental Study - Bellatri Azzahra; Sriati Usman; Andi Patmasari; Jamiluddin (Journal of General Education and Humanities, 2025)
This research explores the impact of using picture series to improve students’ ability to write procedural texts at SMP Negeri 1 Palasa. The primary issue addressed is whether picture series can support students in developing writing skills, organizing ideas, and maintaining motivation during writing activities. The study employed a pre-experimental design using a one-group pre-test and post-test approach involving 20 ninth-grade students selected through single-class sampling. The research was conducted over six sessions, comprising a pre-test, instructional treatment, and a post-test. Data were collected through writing assessments administered before and after the intervention and analyzed using paired sample t-tests. The results indicated an increase in the average score from 60.12 in the pre-test to 68.00 in the post-test. Statistical analysis showed that the calculated t-value (3.44) exceeded the critical t-value (2.36) at a 0.05 significance level with 20 degrees of freedom. These findings suggest that using picture series significantly enhances students’ performance in procedural writing, highlighting its effectiveness as a teaching strategy.